Prevalence of hypertension in children with early-stage ADPKD - Massella, Laura; Kirchner, Marietta; Lutz, Teresa; Schaefer, Franz; Wühl, Elke (Clinical journal of the American Society of Nephrology, 2018)
Visual Overview - Download figureOpen in new tabDownload powerpoint - - Background and objectives Autosomal dominant polycystic kidney disease is the most common inheritable kidney disease, frequently thought to become symptomatic in adulthood. However, patients with autosomal dominant polycystic kidney disease may develop signs or symptoms during childhood, in particular hypertension. Although ambulatory BP monitoring is the preferred method to diagnose hypertension in pediatrics, data in children with autosomal dominant polycystic kidney disease are limited. - Design, setting, participants, & measurements Our retrospective multicenter study was conducted to collect ambulatory BP monitoring recordings from patients with autosomal dominant polycystic kidney disease age <18 years old. Basic anthropometric parameters as well as data on kidney function, BP treatment, and kidney ultrasound were also collected. - Results Data from 310 children with autosomal dominant polycystic kidney disease with a mean age of 11.5±4.1 years old were collected at 22 European centers. At the time when ambulatory BP monitoring was performed, 95% of children had normal kidney function. Reference data for ambulatory BP monitoring were available for 292 patients. The prevalence rates of children with hypertension and/or those who were treated with antihypertensive drugs were 31%, 42%, and 35% during daytime, nighttime, or the entire 24-hour cycle, respectively. In addition, 52% of participants lacked a physiologic nocturnal BP dipping, and 18% had isolated nocturnal hypertension. Logistic regression analysis showed a significant association between a categorical cyst score that was calculated on the basis of the number of cysts >1 cm per kidney and daytime hypertension (odds ratio, 1.70; 95% confidence interval, 1.21 to 2.4; P=0.002), nighttime hypertension (odds ratio, 1.31; 95% confidence interval, 1.05 to 1.63; P=0.02), or 24-hour hypertension (odds ratio, 1.39; 95% confidence interval, 1.08 to 1.81; P=0.01). Kidney length, expressed as SD score, was also significantly associated with nighttime hypertension (odds ratio, 1.23; 95% confidence interval, 1.06 to 1.42; P=0.10). - Conclusions These data indicate high prevalence of hypertension in children with autosomal dominant polycystic kidney disease starting at young ages.